SPATIO-TEMPORAL VARIATIONS OF YELLOWFIN TUNA CAUGHT BY HANDLINE IN THE INDIAN OCEAN, SOUTH OF NUSA TENGGARA - ROY KURNIAWAN; Bram Setyadji; Suciadi Catur Nugroho; Teja Arief Wibawa (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2020)
One of the main targets from small-scale handline tuna fishery is yellowfin tuna (Thunnusalbacares), where most, if not all of its operation depended heavily on the installment of the fish aggregating device (FAD). The objective of the study was to investigate the spatial and temporal distribution of catch and size of yellowfin tuna from FAD-associated handline fishery. The study was conducted from January to December 2018 with main observation location was in Labuhan Lombok fishing port, West Nusa Tenggara. The results showed that the highest catch rate was obtained during April-June, followed by the frequent emergence of large yellowfin tuna (>100 cm FL). On the other hand, January-March was considered as a low season, where most of the catch was dominated by juvenile yellowfin tuna (<50 cmFL). The spatial distribution of yellowfin tuna abundance is closely related to the presence of FADs, where all fishing operations are carried out around FADs. Also, aggregation of fish was more likely influence by temporal variation rather than the quantity of FAD. More abundant yellowfin tuna were found during the east monsoon (April-June) compared to another season where less fish occurred.